A Comparison Of Single And Multiple Jets In Terms Of Aeration Efficiency. Issue 1 (1st February 2023) - Puri, Diksha; Sihag, Parveen; Kumar, Rajesh
Abstract: Water treatment is required to meet the needs of an ever-increasing population. A variety of aeration strategies can be used to aerobically maintain liquid waste by supplying an adequate supply of oxygen to microorganisms present in the organic content of wastewater. In this investigation, seven different screens with single and multiple holes totaling 30.75 cm2 were used. The screens were designed to accommodate a variety of jet counts. The influence of variables such as the number of jets, discharge, and froude no on aeration efficiency was studied. The discharge rates of 4.750 l/s, 3.84 l/s, and 3.41 l/s were tested on each screen. The results suggest that the variables studied had a significant impact on aeration efficiency.